A Complex Case of Emphysematous Cystitis in a Peritoneal Dialysis Patient. (8th July 2021) - Okello, Christina; Raj, Rajesh
Abstract : Emphysematous cystitis (EC) is a relatively rare condition characterized by gas formation in the bladder wall and/or lumen. We report a case of emphysematous cystitis with a bladder perforation in an 84-year-old male on peritoneal dialysis who presented with fever, dysuria, hematuria, and hypotension. Gas in the bladder wall, as well as a small perforation in the roof of the urinary bladder, was seen on the abdominal CT scan. The causative organism identified was Escherichia coli. The patient recovered with broad-spectrum antibiotics along with bladder irrigation and drainage. After initial bladder washouts, peritoneal dialysis was continued with close monitoring. Early antibiotic therapy and a conservative approach to the management of small intraperitoneal bladder perforations were effective in this patient. Peritoneal dialysis was uninterrupted for the duration of the admission and after discharge.